Experimental Study on Thermal Expansion Property of Epoxy Mortar in Hydraulic Structure Repairing. Issue 1 (January 2021) - Sun, Yufei; He, Jingjing; Ma, Lingyun; Di, Shengjie; Zhang, Ying; Liu, Jing; Xing, Ruijiao
Abstract: The thermal expansion property of epoxy mortar has a significant effect on the repair effect. Experiments were carried out to study the thermal expansion coefficient of epoxy mortar by changing the type of curing agent, various sand binder ratios and sand etc. The results show that the curing agent has a remarkable effect on the thermal expansion coefficient of epoxy mortar. When the type and content of curing agent are fixed, the influence of sand binder ratio and sand type on thermal expansion coefficient of epoxy mortar is relatively small. It is an effective way to reduce the thermal expansion coefficient of epoxy mortar with excellent curing agent. The research conclusion can provide a reliable basis for hydraulic concrete repairing.